CD4 T-Cell Responses to Herpes Simplex Virus Type 2 Major Capsid Protein VP5: Comparison with Responses to Tegument and Envelope Glycoproteins - Koelle, David M. (American Society for Microbiology, 2000)
We used CD4 lymphocyte clones from herpes simplex virus type 2 (HSV-2) lesions or the cervix and molecular libraries of HSV-2 DNA to define HSV-2 major capsid protein VP5 and glycoprotein E (gE) as T-cell antigens. Responses to eight HSV-2 glycoprotein, tegument, nonstructural, or capsid antigens were compared in 19 donors. Recognition of VP5 and tegument VP22 were similar to that of gB2 and gD2, currently under study as vaccines. These prevalence data suggest that HSV capsid and tegument proteins may also be candidate vaccine antigens.